2005
DOI: 10.1152/ajpheart.00479.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of estrogen receptor-α protects the in vivo rabbit heart from ischemia-reperfusion injury

Abstract: The estrogen receptor (ER) mediates estrogenic activity in a variety of organs, including those in the reproductive, cardiovascular, immune, and central nervous systems. Experimental studies have demonstrated that 17beta-estradiol (E2) protects the heart from ischemia-reperfusion injury. Two estrogen receptors, ER alpha and ER beta, mediate the actions of estrogen; however, it is not certain which ER mediates the cardioprotective effects of E2. In the present study, the ER-selective agonists 4,4',4''-[4-propyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
96
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 55 publications
5
96
1
Order By: Relevance
“…Similar findings were obtained in osteoblasts, where estrogen inhibits cytokine production by repressing NF-B activity via the ER␣ (Ray et al, 1994;Galien et al, 1996). Interestingly, a recent study has concluded that it is the ER␣ and not ER␤ that mediates the ability of estrogen to protect against myocardial ischemiareperfusion injury (Booth et al, 2005). Although the precise mechanism of estrogen action was not identified in this study of intact hearts, a protective role of ER␣ in myocardial function is perfectly consistent with the present findings demonstrating ER␣-mediated effects on coronary artery cellular Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Similar findings were obtained in osteoblasts, where estrogen inhibits cytokine production by repressing NF-B activity via the ER␣ (Ray et al, 1994;Galien et al, 1996). Interestingly, a recent study has concluded that it is the ER␣ and not ER␤ that mediates the ability of estrogen to protect against myocardial ischemiareperfusion injury (Booth et al, 2005). Although the precise mechanism of estrogen action was not identified in this study of intact hearts, a protective role of ER␣ in myocardial function is perfectly consistent with the present findings demonstrating ER␣-mediated effects on coronary artery cellular Fig.…”
Section: Discussionsupporting
confidence: 60%
“…It is unlikely that this loss of cardioprotection was related to insufficient doses of 17␤-estradiol and genistein. Regarding 17␤-estradiol, its preischemic administration has been shown to be cardioprotective at 10 g/kg in male rabbits (Hale et al, 1996;Booth et al, 2005), and the same dose administered at the end of 60-min CAO in male dogs has been shown to reduce infarct size (Lee et al, 2004). In the present study, we used a dose of 17␤-estradiol that was already 10 times greater to observe cardioprotection with 20-min CAO.…”
Section: Discussionmentioning
confidence: 92%
“…21,34 Estrogen receptors α and β have been extensively investigated and are vital for the incorporation of bone marrow-derived EPCs in ischemic tissue; the role of the α receptor appears to be more prominent. 11,50 We acknowledge that the EPC culture assay does not completely exclude cells of a non-endothelial lineage, and that FACS analysis could provide additional specificity. However, the maximum amount of blood that can be taken from a mouse (1 ml) is not sufficient for both the EPC culture assay and FACS analysis, and this limitation can be overcome only by pooling blood samples from several mice, which would reduce the statistical power of subsequent analyses.…”
Section: Discussionmentioning
confidence: 99%